Early versus delayed amniotomy with immediate oxytocin after Foley catheter cervical ripening in nulliparous labor induction: A randomized trial. Issue 3 (4th July 2022) - Hasan, Nur Adlyn; Hong, Jesrine Gek Shan; Teo, Ik Hui; Zaidi, Syeda Nureena; Hamdan, Mukhri; Tan, Peng Chiong
Abstract: Objective: To evaluate immediate oxytocin and early amniotomy compared with delayed amniotomy after Foley catheter cervical ripening in nulliparous women on intervention‐to‐delivery interval. Methods: A randomized trial was conducted from September 2020 to March 2021. A total of 140 term nulliparas (70 early amniotomy, 70 delayed amniotomy) with Foley catheter–ripened cervices (dilatation ≥3 cm achieved), singleton fetus, cephalic presentation with intact membranes, and reassuring fetal heart rate tracing were recruited. Women were randomized to immediate titrated intravenous oxytocin infusion and early amniotomy or delayed amniotomy (after 4 h of oxytocin). The primary outcome was intervention (oxytocin)‐to‐delivery interval (h). Results: Intervention‐to‐delivery intervals (h) were mean ± standard deviation 9.0 ± 3.6 versus 10.6 ± 3.5 h (mean difference of 1.4 h) ( P  = 0.004) for the early versus delayed amniotomy arms, respectively. Birth rates at 6 h after oxytocin infusion were 19 of 70 (27.1%) versus 8 of 70 (11.4%) (relative risk, 2.38 [95% confidence interval (CI), 1.11–5.06]; number needed to treat: 7 [95% CI, 3.5–34.4]) ( P  = 0.03), cesarean delivery rates were 29 of 70 (41.4%) versus 33 of 70 (47.1%) (relative risk, 0.88; 95% CI, 0.61–1.28) ( P  = 0.50), and maternal satisfaction on birth process were a median of 7 (interquartile range, 7–8) versus 7 (interquartile range, 7–8) ( P  = 0.40) for the early versus delayed amniotomy arms, respectively. Conclusion: In term nulliparas with cervices ripened by Foley catheter, immediate oxytocin and early amniotomy compared with a planned 4‐h delay to amniotomy shortened the intervention‐to‐delivery interval but did not significantly reduce the cesarean delivery rate. Synopsis: Immediate oxytocin and early amniotomy compared with delayed amniotomy after cervical ripening with Foley catheter in nulliparas shorten the intervention‐to‐delivery interval.